(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Introduction. In recent years, a great emphasis on language assessment has been the main focus of language teachers. Reasonably, it has been a primary issue for decades since its role in the teaching and learning process is central. When assessment is not properly utilized, this can lead to several issues like poor student participation, reduction in student overall performance. There is a strong relationship between assessment and teaching because each depends on another. Teachers’ lack of assessment skills may cause little or no connection between assessment and teaching (Malone, 2011). We believe that language teachers need to take assessment training or participate in language assessment conferences so that they understand how teaching and learning can be made easier with the help of assessment.